Investigating the effectiveness of forensic case formulation recommendations - Vicky Wheable (Psychology, Crime and Law, 2022)
The Offender Personality Disorder Pathway (OPDP) was co-commissioned in 2011 to better manage high-risk offenders likely to have a personality disorder. Within the OPDP, forensic case formulation is used to develop a psychological understanding of each offender’s criminal behaviour, clinical problems, and criminogenic needs. Each formulation concludes with a set of recommendations aimed at addressing the problems and needs identified. However, no research has yet investigated the effectiveness of these recommendations. To address this, the present study used a multiple case-study method to investigate the effectiveness of recommendations generated within 10 OPDP formulations. Two sets of cases were examined: 5 with positive outcomes, and 5 with negative outcomes (known as a ‘two-tailed’ multiple case study). When these two sets of cases were compared, a clear pattern of differences emerged in the relevance, feasibility, utility, and impact of the formulation recommendations made (in favour of cases with positive outcomes). On the basis of these results, a provisional logic model was developed to operationalise the process by which formulation recommendations were hypothesised to have contributed to outcomes in ‘positive’ cases, and where and why this process commonly deteriorated in ‘negative’ cases. Implications of these results and avenues for further study are discussed.